Content-Based Learning on Digital Platforms: Transformation of Learning Resources in the Social Media Era - Risza Presty Rumani (EduTech Journal, 2026)
The rapid development of digital technology has fundamentally transformed the landscape of education, particularly in how learning resources are accessed and utilized. This study examines Content-Based Learning (CBL) within digital platforms, with particular emphasis on the transformative role of social media as an emerging ecosystem for educational content. Employing a systematic literature review methodology, this research synthesized findings from 20 peer-reviewed studies published between 2022 and 2025. The findings reveal that digital platforms, including YouTube, Instagram, TikTok, WhatsApp, and various Learning Management Systems, significantly enhance student engagement, knowledge acquisition, and collaborative learning. Social media platforms function not merely as communication tools but as dynamic spaces for content creation, peer-to-peer knowledge sharing, and informal learning. This study identifies key opportunities including increased accessibility, personalization of learning experiences, and community-driven knowledge ecosystems, while also noting persistent challenges related to information credibility, digital distraction, and the digital divide. The research concludes that the integration of CBL approaches within digital platforms represents a paradigm shift in contemporary education, requiring pedagogical adaptation from educators and critical digital literacy from learners.